Návrh bioplynové stanice - Mészáros, Gabriel (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2011)
Diplomová práce je zaměřena na možnost využití biologicky rozložitelných materiálů (živočišný trus, energetické plodiny, rostlinný odpad) v bioplynové stanici. První část se věnuje mechanizmu tvorby bioplynu. Jsou popsány faktory vplývající na produkci bioplynu, jeho složení, vlastnosti, možnosti využití a potenciální substráty. Další kapitole se zabývá užívanými technologiemi bioplynových stanic. Hlavní část práce se věnuje návrhu konkrétní bioplynové stanice na území Slovenské republiky v Novozámockém okrese. Součástí je zpracování projekčního návrhu, volba jednotlivých komponent a návrhu uspořádání bioplynové stanice. Ekonomické hodnocení zahrnuje vyčíslení investičních a provozních nákladů a zisků z prodeje elektřiny a kompostu.

The master’s thesis is focused on the possibility of using biodegradable materials (animal manure, energy crops, crop waste) in a biogas plant. The first part deals with the mechanism of production of biogas. Described are factors which affect the production of biogas, its composition, properties, utilization and potential substrates. The next chapter deals with the technologies of biogas plants. The main part of the thesis is devoted to a proposal of a specific biogas plant in the Slovak Republic in the Novozámocký district. Included is the processing of design proposal, selection of components and proposal of the layout of biogas plant. The economic evaluation includes quantifying capital and operating costs and profits from the sale of electricity and compost.
Bio-gas power plant
Keywords: Anaerobní fermentace; bioplyn; návrh bioplynové stanice; ekonomika provozu; Anaerobic fermentation; biogas; biogas plant proposal; economic evaluation